Development of Canva-Assisted Media with The CIRC Learning Model for Visual Groups of Junior High School Students - Cahyani, Enny Putri; Hendriana, Heris; Sugandi, Asep Ikin (JRPM (Jurnal Review Pembelajaran Matematika), 2025)
Technological skills in Indonesian society need to be trained in order to be socially competent and able to face challenges in the future. The gap that occurs at this time is the rapid development of technology so that human resources are not ready to optimize it properly. The author designs Canva-assisted interactive learning media integrated with the CIRC (Cooperative Integrated and Reading Composition) learning model so that students as one of the human resources can be motivated in significant technological developments. This research uses a Design Research approach with the stages of Preliminary Study, Formative Evaluation and Summative Evaluation. This research was conducted in one of the Junior High Schools in Cianjur Regency. After a series of stages were carried out, the responses given by students to the media developed in the visual group were in the average range of 4-5. This shows that the learning media developed gets a good response and is feasible to use in learning mathematics, especially building materials. It is hoped that this media can be developed on other materials and can motivate other math teachers.